Edukasi Bioaktif Tumbuhan Dalam Pengelolaan Penyakit Untuk Pembudidaya Ikan di Desa Purworejo, Sragi Kabupaten Pekalongan - Ashari Fahrurrozi; Wijianto Wijianto (BADAN PENERBIT STIEPARI PRESS, 2024)
Community service program (PkM) for the community carried out in Purworejo Village, Sragi District, Pekalongan Regency, Central Java Province. This activity aims to introduce fisheries cultivation to the surrounding community and the application of plant bioactives in fish disease management for aquaculture practitioners. Provide insight and experience regarding implementation, management and utilization to increase fish resistance from disease, and produce economically valuable and profitable production results. The method used in this program is assistance to participants through presentations and outreach, application of plant bioactives and their management, to evaluation through questionnaires. The stages of service activities are carried out through education in the meeting room, demonstration of plant bioactive applications, as well as evaluation of the materials and demonstrations that have been provided. With questionnaire percentage results ≥80% in the good category. Therefore, it can be interpreted that the material presented is useful, which shows that the material and performances presented are right on target.